Nursing of a case of drug-induced hypersensitivity syndrome complicated with multiple organ failure undergoing continuous renal replacement therapy (1例药物超敏反应综合征合并多脏器衰竭行连续性肾脏替代治疗的护理) - SONG Xiaoxiu (宋晓秀); XIAO Li (肖莉) (中西医结合护理)
This article summarized clinical data and nursing management of a patient with drug-induced hypersensitivity syndrome characterized by toxic epidermal necrolysis and dermatitis combined with multiple organ failure treated with continuous renal replacement therapy (CRRT). Given the complex illness condition of the patient, a comprehensive evaluation on nursing risks was carried out before CRRT. In addition to enhance the nursing cooperation in CRRT, nurses had improved the nursing interventions on symptoms of multiple organ failure, catheter maintanence, skin care, diet guildance and health education during the hospitalizaiton. After effective treatment and meticulous care, the patient's skin condition and psychological state were improved. (本文总结1例以中毒性表皮坏死松解症为表现特征的药物超敏反应综合征样皮炎合并多脏器衰竭患者行连续性肾脏替代治疗(CRRT)的护理经验。患者病情复杂, 入院后积极完善评估和检查, 采取CRRT治疗, 同时加强脏器衰竭护理、CRRT护理、管路护理、皮肤护理, 做好饮食指导和健康宣教, 积极预防并发症, 患者的皮损明显减轻, 生命体征相对恢复稳定。)